MUBTADA’ (TOPIC) DAN KHABAR (COMMENT) DALAM KITAB SAFINATUN NAJA KARYA SYEIKH SALIM BIN ABDULLAH BIN SAID BIN SUMAIR AL HADRAMIY (ANALISIS SINTAKSIS) - Ramadlon, Anang; Busri, Hasan; Elmubarok, Zaim (Universitas Negeri Semarang, 2021)
Mubtada 'isim marfu' which is free from amil lafadz. While khabar (comment) is an isim marfu' to complete the meaning of mubtada' (topic). This research is a qualitative research with library research research design. The instruments used in this study were data cards and recapitulation sheets. Data collection techniques using documentation techniques. The data analysis technique uses the distributional method for the direct element, and the data validity check technique uses the credibility test technique to increase persistence. Based on the research conducted by the researcher, the researcher found 279 data in the form of mubtada (topic) and khabar (comment), because the amount of data was almost the same, the researcher took 89 data for in-depth analysis. Of the 89 mubtada'(topic), 89 are mubtada'(topic) sharih and none of the mubtada'(topic) muawwal. Based on the terms of use, there are no mubtada '(topics) that are obligatory mahdzuf and 3 may be mahdzuf, 82 are obligatory muqaddam and 2 may be muqaddam, and 1 is obligatory muakhkhar and 1 may be muakhkhar. Based on the grammatical markers, it consists of 75 mubtada' (topic) with the grammatical marker dlammah, none with the grammatical marker alif, waw, and nun, and 14 mubtada' (topic) which occupies the function of mubtada' (topic) (machal rafa'). And of the 89 khabar (comments), 64 are mufrad khabar (comments) and 25 are ghairu mufad khabar (comments). Based on the terms of use, there is no khabar (comment) that is obligatory and can be mahdzuf, 1 is mandatory and can be muqaddam, and 85 is obligatory muakhkhar and 2 may be muakhkhar.